Conversion of Natural Bentonite into Effective Adsorbents for Removing of Pb2+ Ions from Wastewater - Salih, Ali Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2021)
Adsorption is an effective techniques using for removing heavy metal contamination from wastewater. In order to study the capacities of both natural and modified bentonite (synthetic analcime zeolite (ANA)) samples to remove lead ions, batch adsorption experiments of Pb2+ were conducted under various conditions. Most essential parameters such as initial solution pH, adsorbent mass and contact time were studied. Bentonite clay was activated and went through various thermal and chemical processes. The result from this route shows that zeolite ANA crystals with regular icositetrahedron have been successfully synthesised. The efficiency of both natural bentonite and zeolite ANA converted from natural bentonite and their ability for the reducing of Pb2+ ions from industrial wastewaters have investigated and the results show that heavy metal removal was enhanced with increased initial solution pH, greater mass of absorbent and fast in the in the first hour. The uptake of Pb2+ ions from solution by synthetic zeolite type ANA was improved compared to natural bentonite.
Keywords: Bentonite; Zeolite ANA; Adsorption; Ione exchange; Heavy metals